2009
DOI: 10.2340/00015555-0627
|View full text |Cite
|
Sign up to set email alerts
|

Total Serum IgE as a Parameter to Differentiate Between Intrinsic and Extrinsic Atopic Dermatitis in Children

Abstract: Atopic dermatitis (AD) has been sub-classified into extrinsic and intrinsic types according to the presence or not of allergen-specific IgE antibodies. Although total serum IgE levels are frequently elevated in AD, their potential to predict allergen-specific IgE (asIgE) has rare ly been studied. We investigated 103 children with AD and suspected allergen-specific sensitization. A thorough clinical examination, a structured medical history and total serum IgE and asIgE measurements were performed. Fifty-three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 30 publications
8
36
3
1
Order By: Relevance
“…Total IgE levels and eosinophil counts have long been considered important indexes for AD diagnosis, and elevated total IgE and higher eosinophil counts are commonly observed in patients affected by AD [46]. In this study, the total IgE level was significantly higher in AD patients than in HCs and positively correlated with disease severity, in accordance with previous studies [47].…”
Section: Discussionsupporting
confidence: 81%
“…Total IgE levels and eosinophil counts have long been considered important indexes for AD diagnosis, and elevated total IgE and higher eosinophil counts are commonly observed in patients affected by AD [46]. In this study, the total IgE level was significantly higher in AD patients than in HCs and positively correlated with disease severity, in accordance with previous studies [47].…”
Section: Discussionsupporting
confidence: 81%
“…Our findings confirmed that 21% of elderly patients had AD with low total IgE and were not allergic to common allergens. These values are slightly higher than those of other reports (5–15%), which have investigated younger populations [9,14,15]. It is possible that AD with low total IgE is more prevalent in elderly AD patients.…”
Section: Discussioncontrasting
confidence: 54%
“…The total IgE levels and the Eczema Area and Severity Index (EASI) score were examined on the hospital visit and the average values were compared between the patient groups (those who have experienced deterioration and those who have not experienced any noticeable changes). In addition, we classified the patients into those who showed low total serum IgE levels (<200 kU/l), with the absence of associated respiratory diseases, a lack of allergen specific serum IgE antibodies and negative skin prick tests into the intrinsic AD (IAD) group 11 . We compared the difference in the prevalence of symptom aggravation in association to pregnancy or menstruation between the IAD patients and the extrinsic AD (EAD) patients.…”
Section: Assessment Of the Influence Of Pregnancy And The Menstrual Cmentioning
confidence: 99%